Critical theory in prestigious academic environments: a first-generation student's chronicle - Sadi, Merav Nakar; Ergas, Oren (Critical studies in education, 2023)
The past 50 years have witnessed a growing presence of critical theory within different social science academic departments across the western world. The joint existence of a theory committed to exposing and criticizing various inequalities of the social order within academic institutions based on traditional hierarchies and prestigious arrangements is the starting point of this paper. It is also the viewpoint from which I probe into my own experience as a first-generation student of Middle Eastern background who experienced intensive socialization processes - from undergraduate to PhD studies in Sociology - at two sociology departments both committed to critical theory. Using the method of autoethnography aided by a critical friend, I explain how, within its academic residency, critical theory's normative inclination to 'empower' marginalized subjects such as myself contained sweeping assumptions and inner contradictions that resulted in disenchantment and an overall estrangement from critical theory and academic writing altogether. I argue that selective acceptance and ongoing questioning of this discourse can revive a more constructive relations of first-generation students with their marginalized identities, and even turn them into valuable resources for writing and educational value.